Penal Mediation by Police Investigators on Fraud and Embezzlement Cases in the Integrated Criminal Justice System - Kristianingsih, Ekawaty (Global Writing Academica Researching & Publishing, 2021)
In Indonesia, investigators act as mediators in resolving criminal cases, and investigators perform this role purely based on their discretion but consider the need for this institution to be formalized. This institution was formalized in the Head of the Indonesian National Police's Telegram Letter No. Pol: B/3022/XII/2009/SDEOPS dated December 14, 2009, regarding Case Handling Through Alternative Dispute Resolution (ADR) (STR Kapolri 3022/2009), that the use of ADR in resolving criminal cases can occur if the litigants (victim and perpetrator) agreed. The settlement will only be carried out under professional and proportional legal procedures if the parties have no agreement. STR Kapolri 3022/2009 limits what crimes can be resolved through ADR, so the following problems arise. How is the power of law and legal certainty in applying penal mediation in cases of fraud and embezzlement carried out by police investigators? How should penal mediation be realized in an integrated criminal justice system? This research uses normative juridical or doctrinal law research, systematically expounds on specific legal categories' regulations, and analyzes the relationship between several principles. Then from the study results on the components of the legal structure, penal mediation in an integrated criminal justice system is realized by: (i) establishment of a penal mediation institution; (ii) synchronization of law enforcement and courts in carrying out penal mediation. (iii) Finally, the legal culture component needs to be reformulated by adjusting the penal mediation to each region's prevailing culture and values.